The occurrence of Nosema apis (Zander), Acarapis woodi (Rennie), and the Cape problem bee in the summer rainfall region of South Africa - Swart, Dawid Johannes (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
The occurrence of Nosema disease, tracheal mites and the "pseudo-parasitic" behaviour of Cape honeybee workers when placed amongst African honeybees "“ known as the Cape Bee Problem "“ were studied over a 18 month period. Three surveys, approximately 6 months apart were done. The aims of this study were to establish the distribution and severity of the diseases and compare the disease with the presence of the Cape Bee Problem. Before this survey commenced European Foul Brood disease, Sacbrood (virus), Nosema, Brood nosema, and Tracheal mite have sporadically been reported in the summer rainfall region of South Africa. In the first survey 1005 colonies in 61 apiaries were surveyed, 803 colonies in 57 apiaries in the second, and 458 colonies in 41 apiaries in the third. Samples for disease and parasite analysis were taken at 4 colonies per apiary. Ten colonies per apiary were inspected for Cape Problem Bees, and samples of workers were collected and dissected at each of these colonies. Even with the addition of apiaries to 'fill-up' lost colonies during the second survey, 63% of all colonies were lost by the third survey. There was only a small difference in colony loss between sedentary and migratory beekeepers of 22% compared to 27%. Nosema was more prevalent amongst commercial beekeepers and increased in migratory operations during the survey period. The percentage of colonies infected increased during the survey period from 23% to 32% to 34%. The placement of colonies in Eucalyptus plantations may boost infection. Trachea mites seem to have spread quite rapidly in South Africa since its discovery. This parasitic mite was present in all regions, although in low numbers in three most northern regions. Sedentary colonies had higher levels of infestation than migratory colonies. The number of colonies infested diminished over the survey period, which may be a result of general colony loss. The Cape Problem Bee was less of a problem than anticipated. Colonies succumbed to Cape Problem Bees in all regions. When beekeepers reported high levels of infestation in their bee stocks the colonies would be dead within six months. In apiaries with low infestation the die-out was slower.
Keywords: Nosema apis; Bee culture; Honeybee -- South Africa; Honeybee -- Diseases; Honeybee -- Parasites; Mites